The Gallaghers of Ardmore: Heart of the Sea - Book 3 - Roberts, Nora (New York : Berkley Books, 2014)
"Darcy Gallagher has always believed in the pull of fate, the magic of legend...and the importance of money. She longs to find a rich man who will sweep her away--into a world filled with glamour and adventure, and the exotic life that is her destiny... A wealthy businessman with Irish blood, Trevor Magee has come to Ardmore to build a theater--and to uncover the secrets hidden in his familys past. He thought he had given up on love long ago, but Darcy Gallagher tempts him like no woman ever has. Shes gorgeous and intelligent, and she knows what she wants-- and hes more than willing to give it to her. But as their mutual attraction flares into passion, they look into their hearts--and find out what happens when you truly believe"--Provided by publisher.
Keywords: Ireland -- Fiction; Romance fiction